Design of Image Elements Of The Kalianget Old Town (Salt Industry) Using A Historicism Architecture Approach (Case Study: Kalianget, Sumenep, Indonesia) - Ayu, Erlita Maynanda; Koesoemawati, Dewi Junita; Revana, Dano Quinta (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2025)
The image of a city is inextricably linked to the identity of certain visual elements that serve to distinguish it from other cities. Kalianget Old Town is home to a multitude of historical edifices that have come to symbolise the city at various points in its history. However, the architectural style of the building differs from its original condition due to previous restoration work, which has the effect of reducing the impression that the Kalianget Old Town Area has historical value for city observers. This research differs from previous studies in that it employs the Historicism Architecture approach to examine the design of buildings within the context of city image. This approach is grounded in the seminal work of Kevin Lynch, who posited that the perception of an urban environment is shaped by the elements that comprise its image. The methodological approach employed is that of descriptive qualitative research, which involved the identification of image elements within Kalianget Old Town. These included the identification of the path, edges, districts, nodes and landmarks. The subsequent step involved the application of Historicism Arcitecture design approach, to reinforce the identity of the city. The design of Historicism Architecture is based on the Dutch Classic Colonial concept, which employs natural colours (grey, brown, white, black and orange) throughout the city image, encompassing the core area of Kalianget Old Town. Additionally, anchor ornaments, boats, carvings and flying horse icons are incorporated into the East Port area, reinforcing the image of this region. These elements are integrated into the cityscape through the use of paths, nodes and edges.